Urine-Derived Stem Cells: The Present and the Future - Xiaoli Ji; Min Wang; Fang Chen; Junmei Zhou (Stem Cells International)
Stem cell research provides promising strategies in improving healthcare for human beings. As a noninvasively obtained and easy-to-culture cell resource with relatively low expense, urine-derived stem cells have special advantages. They have been extensively studied on its proliferation ability and differentiation potential and were being reprogrammed to model diseases during the last decade. In this review, we intend to summarize the latest progress on the research of urine-derived stem cells for its broad application mainly in regenerative medicine and disease modeling, as well as in what is challenging currently. This minireview will highlight the potential application of urine-derived stem cells and provides possible direction of further research in the future.